2000
DOI: 10.1080/14660820052415790
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging (fMRI) clinical studies in ALS - paradigms, problems and promises

Abstract: Functional magnetic resonance imaging (fMRI) provides high-resolution, non-invasive estimates of neural activity detected by a blood oxygen level dependent signal by assessing the increase in blood flow to the local vasculature that accompanies neural activity in the brain. fMRI studies with standard hand motor test (index-thumb opposition, ITO, or pinch) in ALS patients show good test-retest reliability and similar amplitude of signals in ALS patients compared with control subjects. Isometric force can be per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…The MR spectrum is a spectral graph in which the x-axis denotes the unique chemical composition of a metabolite in parts per million (ppm) and the y-axis reflects the concentration of that metabolite. Although the MR spectrum can be generated from any element in the periodic table that has an odd number of protons, biological MR studies are generally confined to those involving the 1 H, 31 P, 13 C, 23 Na, and 19 F protons. Of these, the most commonly studied is proton ( 1 H) nucleus due to its abundance in biological tissue (water and fat) and high sensitivity.…”
Section: Basic Physicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MR spectrum is a spectral graph in which the x-axis denotes the unique chemical composition of a metabolite in parts per million (ppm) and the y-axis reflects the concentration of that metabolite. Although the MR spectrum can be generated from any element in the periodic table that has an odd number of protons, biological MR studies are generally confined to those involving the 1 H, 31 P, 13 C, 23 Na, and 19 F protons. Of these, the most commonly studied is proton ( 1 H) nucleus due to its abundance in biological tissue (water and fat) and high sensitivity.…”
Section: Basic Physicsmentioning
confidence: 99%
“…Since deoxyhemoglobin is paramagnetic, it alters the T2*-weighted magnetic resonance image signal. Therefore, this change leads to an increase in the fMRI signal that has been called the blood oxygenated level-dependent effect [23,79].…”
Section: Functional Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a changed pattern and an anterior shift of activity in ALS were also observed in further cortical areas besides the premotor cortex for various motor tasks. For instance, increased involvement of supplementary motor areas (SMA) (Konrad et al, 2002;2006;Han et al, 2006) and sensorimotor cortices has been seen (Brooks et al, 2000;Han et al, 2006;Stanton et al, 2007a;Mohammadi et al, 2011). Activity in contralateral sensorimotor cortex activity was increased the stronger the physical impairments were in patients .…”
Section: Functional Neuroimaging Of Motor Networkmentioning
confidence: 99%
“…In fMRI studies, ALS patients present higher volumes of activated brain areas in motor tasks compared with healthy controls, thus providing evidence for functional reorganisation and cortical plasticity in MND (Brooks et al, 2000;Lulé et al, 2009). Konrad et al observed this in eleven ALS patients (Konrad et al, 2002) who performed a simple finger flexion task with 10% of each individual´s maximum grip force.…”
Section: Functional Neuroimaging Of Motor Networkmentioning
confidence: 99%